Urban structure and urban growth - Guttenberg, Albert A. (Journal of the American Institute of planners, 1964)
Summary : Urban structure is construed here as the result of a community effort to overcome distance between residents and required facilities. The elements of structure are identified, the mutual influences of urban structure and urban growth are considered, and there is an effort made to demonstrate the dynamic inter dependency of various urban structural phenomena by analyzing the effects of a change in transportation efficiency. However, the relationships presumed to hold here are as yet largely hypothetical and require further investigation. This article is timely in view of the current crisis in metropolitan structure occasioned mainly by rising automobile ownership.
Urban structure -- Urban structure and urban growth -- Translocation.
Photocopy.
Keywords: Cities and towns -- Growth. -- United States